2012
DOI: 10.1016/j.amepre.2012.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Aid-Assisted Decision Making and Colorectal Cancer Screening

Abstract: Background Shared decision-making (SDM) is a widely recommended yet unproven strategy for increasing colorectal cancer (CRC) screening uptake. Previous trials of decision aids to increase SDM and CRC screening uptake have yielded mixed results. Purpose To assess the impact of decision aid–assisted SDM on CRC screening uptake. Design RCT. Setting/participants The study was conducted at an urban, academic safety-net hospital and community health center between 2005 and 2010. Participants were asymptomatic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 44 publications
4
77
1
Order By: Relevance
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Two of the articles described different outcomes from one RCT. 31,32 Thus, we considered these two papers one intervention, resulting in a total of 18 interventions with data. The results describe select studies from our review that highlight the types of health conditions, populations studied, DA type and delivery mode, and cultural tailoring used.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Two of the articles described different outcomes from one RCT. 31,32 Thus, we considered these two papers one intervention, resulting in a total of 18 interventions with data. The results describe select studies from our review that highlight the types of health conditions, populations studied, DA type and delivery mode, and cultural tailoring used.…”
Section: Resultsmentioning
confidence: 99%
“…21,29 Pre-visit patient-level interventions in patients of lower socioeconomic status, which have been effective in increasing CRC screening discussions/recommendations, include activation counseling, 31,32 computer-delivered tailored intervention 33 and decision aids. 34 Modest increases (7-27 %) in CRC discussions and/or recommendations with these interventions have been reported. [31][32][33][34] Our current study is unique in targeting both physicians and patients; few prior studies have done so.…”
Section: Discussionmentioning
confidence: 99%
“…34 Modest increases (7-27 %) in CRC discussions and/or recommendations with these interventions have been reported. [31][32][33][34] Our current study is unique in targeting both physicians and patients; few prior studies have done so. 21,35,36 Aragones et al recently showed that a CRC educational video and brochure in Spanish and a patient-delivered physician reminder was associated with a trend toward an increase in physician CRC recommendation rate and a significant increase in CRC test completion.…”
Section: Discussionmentioning
confidence: 99%
“…Shared decision-making processes assisted by decision aids increase colorectal screening uptake, reduce decisional conflict by helping patients identify a preferred screening option, and enhance patient knowledge and satisfaction [7,8]. Although these interventions have increased colorectal cancer screening, the overall impact was relatively modest with no effect on further implementation of shared decision-making processes in cancerscreening practices [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Shared decision-making processes assisted by decision aids increase colorectal screening uptake, reduce decisional conflict by helping patients identify a preferred screening option, and enhance patient knowledge and satisfaction [7,8]. Although these interventions have increased colorectal cancer screening, the overall impact was relatively modest with no effect on further implementation of shared decision-making processes in cancerscreening practices [8,9]. While 70% of patients preferred to engage in shared decision making for preventive health decisions, only 47% indicated that a shared decision-making process occurred during their visit for colorectal cancer screening [9], thus indicating a lack of concordance between patient preferences for shared decision making and the colorectal cancer screening process [9].…”
Section: Introductionmentioning
confidence: 99%